Development of cognitive behavior counseling guidebook with bibliocounseling techniques to improve junior high school student academic motivation - Idayanti, Ni Luh; Dantes, Nyoman; Gading, I Ketut; Dharsana, I Ketut; Suranata, Kadek (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
Learning motivation greatly affects student success in receiving lessons and greatly impacts the improvement of student learning outcomes. This study aims to produce a guidebook design, determine the validity of the content, know the practicality, and test the effectiveness of cognitive behavior counseling guidebooks with bibliocounseling techniques to increase the motivation to learn junior high school students. The method used is research and development (research and development) with a 4D model (Four D) developed by Thiagarajan (1974) which is limited to content validation testing. Three experts and five counselling guidance practitioners were involved to assess the feasibility of the guidebook. Test the validity of the contents of the guidebook using the content validity ratio (CVR) and content validity index (CVI) of Lawshe (1975). The analytical technique used to test the effectiveness of cognitive behavior counseling guidebooks with bibliocounseling techniques to increase student learning motivation is using Posttest – Only Control Group Design. The design of this shape uses a comparison, grouping is done randomly and no pre-test is held. The results of this study show that (1) produce cognitive behavior counseling guidebooks with bibliocounseling techniques to increase the motivation to learn junior high school students. (2) The results of the CVR analysis obtained a value of 24.7 and a CVI value of 0.88, this shows that the guidebook is valid. (3) The practical test of the guidebook on the assessment of 5 guidance and counseling practitioners obtained an average score of 89% (practical), which means that this guidebook is practical for use by guidance and counseling teachers. (4) The effectiveness of the guidebook obtained the values of the experimental group and the control group Sig. (2-tailed) 0.000 < 0.05. Based on these results, it can be concluded that the implementation of cognitive behavior counseling guidebooks with bibliocounseling techniques is effective in increasing the motivation to learn junior high school students.